Populist Attitudes, Political Trust, and External Political Efficacy: Old Wine in New Bottles?. (February 2020) - Geurkink, Bram; Zaslove, Andrej; Sluiter, Roderick; Jacobs, Kristof
Substantial scholarly attention has been devoted to explaining why voters support populist parties. Recently, a new concept has been introduced to gauge populism among voters and to explain voting for populist parties: populist attitudes. However, some researchers regard populist attitudes as simply another measurement of existing and established concepts such as political trust and external political efficacy. Using data from the Netherlands (2018), this article addresses the relationship between these concepts, both theoretically and empirically. This article examines whether political trust, external political efficacy, and populist attitudes tap into different latent dimensions. Using a confirmatory factor analysis, we show that populist attitudes are not old wine in new bottles and that they tap into different underlying attitudes than political trust and external political efficacy. Furthermore, we show that the three measures are not only different constructs but also relate differently to populist voting preferences.